Hubungan Asupan Kalsium dengan Intensitas Dismenore Primer pada Remaja - Vebby Grace Carolina; Arleen Devita (Fakultas Kedokteran Universitas Trisakti, 2022)
BackgroundPrimary dysmenorrhea is lower abdominal pain happening during menstruation which is not associated with other diseases or pathology, mostly experienced by adolescents around the world, including in Indonesia. Calcium intake is considered to affect decreasing the intensity of primary dysmenorrhea. Lack of calcium can cause muscle spasms and contractions. However, the average daily intake of calcium in adolescents in Indonesia is still below the recommended adequacy rate. This study aimed to assess the correlation between calcium intake and the intensity of primary dysmenorrhea in adolescents. MethodsThis study was done from March 2019 until January 2020; Analyzed the correlation between calcium intake and intensity of primary dysmenorrhea in 62 adolescents. Calcium intake was assessed using a semi-quantitative food frequency questionnaire, while the power of primary dysmenorrhea was assessed using a Visual Analogue Scale questionnaire. ResultsThere were 45.2% of adolescents experienced moderate and severe primary dysmenorrhea. In addition, 51.6% of adolescents experienced less calcium intake, with an average of 804.9 mg per day. The results showed a correlation between calcium intake and the intensity of primary dysmenorrhea (p = 0.000). ConclusionsCalcium intake is related to the intensity of primary dysmenorrhea. While calcium intake in adolescents is still lacking, it is recommended to consume adequate calcium intake.